(untitled) - Wengroff, Jake (Hoboken, N.J., 2002)
The Definitive Guide to the Online Bond Market provides a comprehensive overview of the marketplace, and identifies key players and emerging strategies for buying bonds online. Readers will walk through the entire transaction process for each of the primary platforms with the help of expert analysts, and learn more about accessing and trading bonds online through anecdotal examples, case studies, and perspectives from experienced online bond traders. Covering all fixed income instruments available to investors, E-Bonds is a valuable reference for anyone looking to trade bonds over the Internet.
Keywords: Bonds,Electronic trading of securities,Chứng khoán,Thương mại điện tử của chứng khoán; Data processing,Xử lý dữ liệu; United States